Analysis of the curriculum for teaching english in secondary education of the Language Department of the University of El Salvador - Peñate Morales, Oscar Armando; Gálvez Chicas, José Ricardo (1984)
The present work is focused on one of these last problems; the graduates of the "PROFESORADO EN EL IDIOMA INGLES" major of the University of El Salvador are trained to teach English, however, they are obliged, when working in high school, to teach humanistic subjects. In fact, many graduates are presently teaching the humanistic subject of literature, sociology, philosophy, aesthetics, social studies, psychology, tec. some others have has to teach subjects included in the branch of sciences such as mathematics, biology, and administration.